Drivers of depopulation and spatial interdependence in a regional context - Alamá-Sabater, L.; Budí, V.; Roig-Tierno, N.; García-Álvarez-Coque, J.M. (Cities, 2021)
There is a growing consensus on the need to propose specific policies to tackle the ongoing population decline in extensive rural areas of Southern Europe. Developing policies to target this issue requires assessment of the spatial, economic and structural conditions that explain why a municipality experiences depopulation. This study explores the drivers of population growth in the municipalities of the Mediterranean region officially known as the Comunitat Valenciana in Spain. This region is relatively urbanized, so the study allows to explore the spatial interdependence between municipalities that belong to urban and rural areas, some of them subject to significant depopulation. The study's findings, based on a spatial approach, help explain the population growth of municipalities based on their interdependence with neighbouring communities. A population growth model is defined drawing on several dimensions related to population dynamics: accessibility, economic conditions, public facilities and services, natural amenities, and degree of urbanization. The findings show that population dynamics in a given municipality are influenced by its surrounding municipalities, suggesting that policies focusing on clusters of local administrative units can be central to prevent the depopulation of certain areas. •We test the influence of indicators used by policymakers: economic conditions, services and accessibility on population growth•It is proposed a model that capture spatial connections between municipalities•With an exploratory spatial data analysis (ESDA), we study the spatial structure of population growth among municipalities•To analyse the spread effects across municipalities we grouped municipalities according to the risk of depopulation•Factors selected by policymakers to define municipalities at depopulation risk are consistent with economic theory